2018
DOI: 10.22180/na221
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Induced Synthesis of Zn-Al Layered Double Hydroxide Nanostructures towards Efficiently Reducing Fire Hazards of Polymeric Materials

Abstract: Improving the flame retardancy of polymeric materials is an imperative yet challenging task without deteriorating their intrinsic properties. Herein, we reported a facile approach to grow zinc-aluminum layered double hydroxide (Zn-Al LDH) nanostructures on the surfaces of polymer substrates in order to overcome their high fire hazards. CO 2 induced growth of Zn-Al LDH allowed slow and homogeneous nucleation, leading to the as-synthesized Zn-Al LDH with ultra-large size (several microns) and perfect hexagonal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…In addition, the surface of the MgAl-LB had a white film. It was found by SEM that the surface microscopic morphology of MgAl-LBs has ab-oriented hexagonal platelets compared with untreated bamboo (Figures 5(b)-5(g)), which is similar to the structural appearance reported by other researchers [12,14,19,20]. In addition, it was found that the MgAl-LDHs on the surface of MgAl-LBs gradually became denser and denser as the reaction time prolonged (Figures 5(c)-5(g)).…”
Section: Observed Morphology and Growth Mechanismsupporting
confidence: 86%
See 1 more Smart Citation
“…In addition, the surface of the MgAl-LB had a white film. It was found by SEM that the surface microscopic morphology of MgAl-LBs has ab-oriented hexagonal platelets compared with untreated bamboo (Figures 5(b)-5(g)), which is similar to the structural appearance reported by other researchers [12,14,19,20]. In addition, it was found that the MgAl-LDHs on the surface of MgAl-LBs gradually became denser and denser as the reaction time prolonged (Figures 5(c)-5(g)).…”
Section: Observed Morphology and Growth Mechanismsupporting
confidence: 86%
“…Liang et al introduced 5.0 wt% MgAl-LDH and 5.0 wt% melamine pyrophosphate to medium density fiberboards and found that the peak heat release rate (PHRR) and mean heat release rate (MHRR) were reduced by 27.9% and 7.5%, respectively, compared to those of samples with 3.3 wt% MgAl-LDH and 6.7 wt% melamine pyrophosphate [13]. Wang et al reported the synthesis of ZnAl-LDH coating on the surface of wood to enhance the fire resistance of wood [14]. However, as far as we know, no report currently exists on the flame retardancy of bamboo used by MgAl-LDH.…”
Section: Introductionmentioning
confidence: 99%
“…Yao et al [ 180 ] applied nanomagnesium aluminium layered double hydroxide (Mg–Al LDH) to bamboo in an in situ one-step process and found that the total heat release and total smoke production were reduced by 33.3% and 88.9%, respectively, compared to those of samples without Mg–Al LDH. Wang et al [ 181 ] introduced zinc-aluminum layered double hydroxide (Zn–Al LDH) nanostructures to wood and found that the peak heat release rate (PHRR) and total smoke production were reduced by 55% and 47%, respectively, compared to those of the pristine wood [ 181 ]. Nanostructured carbon materials such as graphene was also proven to have a great potential to be used as an effective fire retardant in wood and wood-composite materials for surface protection against fire [ 182 ].…”
Section: Applicationsmentioning
confidence: 99%
“…Nitrogen-based FRs, such as melamine cyanurate (MC) and guanidine phosphate (GP), generate nonflammable gases and effectively suppress the flames during combustion. Furthermore, the use of nanocomposites that contain nanofillers, like layered double hydroxides (LDHs) and graphene oxide (GO), has demonstrated potential as effective flame retardants and smoke suppressants for RPUF composites [37,38]. These nanofillers have a large surface-area-to-volume ratio, improving their ability to interact with the polymer matrix and impede the spread of flames.…”
Section: Introductionmentioning
confidence: 99%